(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Pediatric hematology-oncology patients are assumed to be predisposed to severe COVID-19 disease and complications, but robust data from low- and middle-income countries is lacking. This study was designed with the primary objective of finding the prevalence and outcome of COVID- 19 in children with hematological or oncological diseases. Clinical characteristics of COVID-19, outcomes in terms of need for respiratory support, intensive care, mechanical ventilation or mortality, delay in therapy, and use of COVID-19 directed therapy were analyzed. Method: Retrospective review of all children with hematological or oncological diseases with confirmed COVID-19 managed at Patan Hospital from Jan 2020 to Sep 2021. Patients were screened according to the hospital screening protocol. The clinical characteristics and outcomes of COVID-19 along with the delay in chemotherapy or local therapy were recorded. Result: Twelve children tested positive for SARS- CoV-2 during the study period, and one had reinfection with COVID-19, 9(75%) were oncology patients, while 3(25%) were hematology patients. Fever (83.3%) was the most common symptom, followed by cough (58.3%). Four (33.3%) children had mild infections, and 4(33.3%) had severe infections. Eight oncology patients had delays in starting or continuing chemotherapy or undergoing surgery due to COVID-19. The median duration of delay was 10.5 d (range-7-21 d). The delay in therapy in patients with COVID-19 was significant in comparison to children without COVID-19. Conclusion: The majority of pediatric hematology-oncology patients recovered from COVID-19 without sequelae. There was a delay in providing treatment to oncology patients due to changing protocols.